Innovation policy of European chemical companies with special focus on large companies - Das, Supriyo; Brunet Icart, Ignasi (Revista Internacional de Organizaciones, 2015)
According to Arora et alii (1998), the chemical industry is one of the largest and most R&D-intensive manufacturing sectors in all the advanced economies, and its innovative patterns and productivity growth processes can have profound impacts on economic growth as a whole. The European chemical industry supplies virtually all sectors of the economy and accounts for 17.8% of the total sales of chemicals in the world. This paper gives an overview of the European chemical industry and the changing scenario of the world chemical industry by focusing on the top fifteen chemical companies in Europe. It describes the current problems this industry is facing in Europe especially after the economic crisis and shows that the region and the top companies are investing in R&D to bring about innovation and overcome the current challenges. It shows that R&D spending in absolute terms has hardly changed over the years and that the industry is still globally the largest investor in R&D activities. In terms of R&D, BASF has made the greatest investment followed by Bayer and Syngenta, while R&D intensity is highest for Syngenta and Bayer. BASF and Bayer have made most patent applications and have also had the highest number of patents granted. The quality of research in most chemical companies is very high and most of the large European companies make their first patent application in Europe rather than elsewhere. All the large chemical companies use Merger & Acquisition (M&A) to gain access to innovation. Industry-academia collaboration is one way to generate innovation in the chemical industry in Europe. Chemical clusters and the geographical distribution of chemical companies play a significant role in generating innovation.